Penerapan Pendidikan Islam Pada Program Ekstrakurikuler Tapak Suci di MTs Swasta Zia Salsabila - Aisyah, Aisyah Azzahra; Mavianti, Mavianti (LP. Ma'arif Janggan Magetan, 2024)
Education is a vital component of life. It seeks to maximize each student's potential to become a human being who fears and believes in God Almighty, who possesses noble character, who is healthy, intelligent, capable, creative, independent, and who grows into a responsible, democratic citizen. The purpose of this study is to learn more about how Islamic education is being implemented at MTs Swasta Zia Salasabila in the Tapak Suci extracurricular program. Qualitative research is the kind that this is. The researcher carried up this study by seeing firsthand how Islamic education is implemented at MTs Swasta Zia Salsabila's extracurricular Tapak Suci activities. In addition to doing in-person interviews with the Tapak Suci extracurricular teachers and principal, wherein the school emulates the actions of the Muhammadiyah ortom, specifically Tapak Suci, even though the school itself is not one of the Muhammadiyah ortoms. The principal, the Tapak Suci Extracurricular Teachers, and the kids who took part in the extracurricular activities were the study's subjects. The study's findings demonstrate how Islamic education is applied in the Tapak Suci extracurricular program, as demonstrated by the way students' character is shaped by the instillation of values of worship, such as saying hello during ceremonies before engaging in activities, praying before and after training, and arriving on time, following rules, showing respect for elders, and showing respect for one another. Always assess training sessions at the conclusion to address any errors committed and to inspire participants to continue consistently and with enthusiasm in Tapak Suci Extracurricular activities.